Os conceitos de "Cultura Esportiva" e "Habitus Esportivo": Distanciamentos e aproximaçoes - Moreira, Tatiana Sviesk (2016)
This work deals with two concepts which serve as a support for studies on sport: "sport culture" and "sport habitus". We aim to identify points of intersection and differences between them in the Brazilian field of Physical Education. We conclude that sport culture concept corresponds to the descriptive and structural dimensions of culture conformation in relation to sport in contemporary society, marked by the phenomenon of economic globalization. This concept refers to the symbolic conception of culture that understands the meanings and directions assigned to the sport phenomenon and to its practice by different individuals and social groups. The sport habitus gradually acquired through the exposure of social agents to the logic of the sport field, corresponds to a willingness to think, to make sense and to act in this space. Not everything that is culturally produced in sports is incorporated in the form of sport habitus, but the habitus is based on aspects of culture. That is, the sport culture has a plurality of manifestations that are not always incorporated in the form of a habitus. The aspect that differentiates the manipulation of concepts of culture and sport habitus is the analytical focus of each, working with both in a complementary manner might become a theoretical and methodological option that contributes to the enlargement of the analysis.